High-remanence bonding hydrolysis-resistant magnetic nylon material and preparation method thereof
By modifying the phosphoric acid and additive treatment of magnetic materials, combined with benzophenone and hindered phenol structure, the problem of poor interface compatibility in magnetic composite materials is solved, the mechanical and magnetic properties of magnetic nylon materials are improved, and water resistance is enhanced Resolvability and anti-aging properties extend service life.
Patent Information
- Application Number
- CN202411215977.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
Due to the poor interfacial compatibility between magnetic powder and polymer matrix, existing magnetic composite materials have poor dispersion, low mechanical properties, poor magnetic properties, poor hydrolysis resistance and low molding accuracy, and are prone to aging and shorten their service life.
Modified magnetic materials are treated with phosphoric acid and additives to improve the stability and dispersion of composite magnetic powder, combined with benzophenone structure and hindered phenol structure, enhance the compatibility and hydrolysis resistance of the material, and extrude through twin screws The output mechanism is equipped with high residual magnetic bonding and hydrolysis-resistant magnetic nylon material.
It significantly improves the mechanical properties, magnetic properties, hydrolysis resistance, ultraviolet and thermal oxygen aging properties of magnetic nylon materials, and extends the service life.
Smart Images

Figure BDA0005021547290000021 
Figure BDA0005021547290000031 
Figure BDA0005021547290000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic composite materials, and in particular relates to a high remanence bonded hydrolysis-resistant magnetic nylon material and a preparation method thereof. Background Art
[0002] Magnetic composite materials are usually made by mixing magnetic materials with rubber or plastic. Although rubber-based magnetic composite materials have good weather resistance and molding processability, the low hardness of the rubber substrate itself, its impact resistance, easy absorption of foreign matter such as soil, low service life, and complex processing technology limit its application in high-tech fields such as transportation parts, computers, and electronic devices. Magnetic composite materials based on nylon can be processed by injection molding, one-piece molding, high precision, higher processing efficiency, and conducive to large-scale industrialization. It does not require cutting before molding and cutting after molding. At the same time, the product has good surface finish, better wear resistance and impact resistance, and is easy to assemble. At the same time, the magnetic composite materials prepared by injection molding, molding, calendering, extrusion and other processing methods have complex shapes, thin walls, and inserts, which can achieve lightweight, miniaturization, precision and energy saving of electromagnetic equipment, and can meet market demand.
[0003] However, in order to meet the requirements of magnetic properties, the existing magnetic composite materials often have a high amount of magnetic powder added, and the interface compatibility between the magnetic powder and the polymer matrix is poor, so the magnetic powder has poor dispersion in the composite material and is very easy to agglomerate, which will cause some products to have quality problems such as brittle cracking and deformation during the injection molding process. Even if they are made into magnetic composite materials, they will have low mechanical properties and poor magnetic property stability. Therefore, how to improve the residual magnetic properties of plastic magnets, improve the compatibility between magnetic powder and matrix resin, and improve the poor hydrolysis resistance, poor toughness, low mechanical properties, and low molding accuracy of magnetic composite materials has become a technical problem that needs to be solved urgently in this field.
[0004] In addition, affected by factors such as light, heat, oxygen and moisture, magnetic composite materials will undergo changes in physical and chemical properties and gradually age, resulting in weakened magnetism, decreased mechanical properties, changes in appearance, etc., greatly shortening their service life. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a high remanence bonded hydrolysis-resistant magnetic nylon material and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A high remanence bonding hydrolysis-resistant magnetic nylon material, comprising the following raw materials in parts by weight:
[0008] 12-22 parts of base polyamide, 75-85 parts of modified magnetic material, 0.5-1 parts of lubricant, and 2-3 parts of modified filler.
[0009] Furthermore, the base polyamide is one or more of nylon 1010, nylon 12, nylon 11, nylon 612, and nylon 1012.
[0010] Furthermore, the modified magnetic material is prepared by the following steps:
[0011] S1. Add 2,4-dihydroxybenzophenone, 3-chloro-1,2-propylene glycol, potassium carbonate and acetone to a dry four-necked flask, stir and dissolve, then heat to 110°C, keep warm for 4 hours, cool to room temperature after the reaction, concentrate, wash three times by centrifugation with deionized water, then wash three times by centrifugation with anhydrous ethanol, concentrate again, cool, recrystallize the obtained crude product with ethanol, and finally filter and dry to obtain intermediate 1; the amount ratio of 2,4-dihydroxybenzophenone, 3-chloro-1,2-propylene glycol, potassium carbonate and acetone is 17.1g:7.2mL:11.1g:180mL;
[0012] Potassium carbonate is used as an acid binding agent. Under heating conditions, the molar ratio of 2,4-dihydroxybenzophenone and 3-chloro-1,2-propylene glycol is controlled to be 1:1.05-1.1, and the -OH of 2,4-dihydroxybenzophenone and the -Cl of 3-chloro-1,2-propylene glycol undergo a substitution reaction. The reaction process is as follows:
[0013]
[0014] S2, add intermediate 1, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and DMSO (dimethyl sulfoxide) into a dry four-necked flask, stir until completely dissolved, then slowly add concentrated sulfuric acid, stir and heat to 100°C, keep warm for reaction for 3 hours, cool to room temperature after the reaction, add sodium bicarbonate solution for neutralization, shake and stand for stratification, take the organic phase, dry it with anhydrous sodium sulfate, filter, and distill the filtrate under reduced pressure, purify by column chromatography (the eluent is a mixed solvent of cyclohexane and ethyl acetate, and the volume ratio of cyclohexane and ethyl acetate is 1:1), and distill under reduced pressure to obtain intermediate 2; the amount ratio of intermediate 1, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, concentrated sulfuric acid and DMSO is 22.9 g:20.9 g:2 mL:200 mL;
[0015] Under concentrated sulfuric acid and heating conditions, the molar ratio of intermediate 1 and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is controlled to be 1.05-1.1:1, then -OH of intermediate 1 and -COOH of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid undergo esterification reaction, and the reaction process is as follows:
[0016]
[0017] S3, nitrogen gas was blown into a dry three-necked flask for 30 minutes to expel air and moisture in the flask, and then bis[3-(triethoxysilyl)propyl]amine, tetradecane chloride and DMSO were added, and triethylamine was slowly added after stirring to dissolve. After the addition was completed, the temperature was raised to 80°C and stirred for reaction for 3 hours. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure. The mixture was purified by column chromatography (a mixed solvent of benzene and ethyl acetate was selected as the eluent, and the volume ratio of benzene and ethyl acetate was 8:2), and distilled under reduced pressure to obtain intermediate 3; the dosage ratio of bis[3-(triethoxysilyl)propyl]amine, tetradecane chloride, triethylamine and DMSO was 35mL:23.2mL:13.3mL:200mL;
[0018] The molar ratio of bis[3-(triethoxysilyl)propyl]amine and tetradecane chloride is controlled to be 1:1.05-1.1. Under heating, -NH- of bis[3-(triethoxysilyl)propyl]amine and -Cl of tetradecane chloride undergo nucleophilic substitution reaction, and triethylamine is an acid binding agent. The reaction process is as follows:
[0019]
[0020] S4. The dry three-necked flask was purged with nitrogen for 30 minutes to exclude air and moisture, and then intermediate 2, intermediate 3, DMF (N, N-dimethylformamide) and tetraisopropyl titanate were added in sequence, and the temperature was raised to 90°C with stirring, and the reaction was kept warm for 24 hours. After the reaction was completed, it was cooled to room temperature, distilled under reduced pressure, washed with anhydrous ethanol for 3 times, and dried at 80°C for 12 hours to obtain an auxiliary agent; the amount ratio of intermediate 2, intermediate 3, tetraisopropyl titanate and DMF was 35.2g:37.3g:0.051g:240mL;
[0021] Under the catalytic action of tetraisopropyl titanate, the molar ratio of intermediate 2 to intermediate 3 is controlled to be 1.05-1.1:1, and the hydroxyl group of intermediate 2 and the silane group of intermediate 3 undergo the following chemical reaction. The reaction process is as follows:
[0022]
[0023] S5. Add composite magnetic powder, phosphoric acid and acetone to a dry beaker, heat to 40°C, stir and react for 3 hours, filter, wash until the filtrate is neutral, and then dry at 80°C for 6 hours to obtain pretreated magnetic powder; add additives, deionized water and DMF to a dry three-necked flask and stir for 1 hour, then add pretreated magnetic powder, stir thoroughly until mixed, heat to 70°C, stir and react for 1 hour, and after the reaction is completed, dry at 100°C for 12 hours to obtain modified magnetic material.
[0024] Furthermore, the mass ratio of the composite magnetic powder to phosphoric acid is 20:0.02-0.04.
[0025] Furthermore, the mass ratio of the pretreated magnetic powder to the auxiliary agent is 20:0.5-1.
[0026] Furthermore, the composite magnetic powder is a mixture of neodymium iron boron and strontium ferrite in a mass ratio of 1:1.
[0027] Under heating conditions, phosphoric acid can react chemically with iron in the composite magnetic powder to generate an iron phosphate coating layer to improve the stability of the composite magnetic powder. At the same time, hydroxyl groups are introduced on the surface of the composite magnetic powder. The silaneoxy groups in the additives will hydrolyze, condense, and cross-link to form Si-OH and Si-O-Si. Therefore, the hydroxyl groups on the surface of the composite magnetic powder can form chemical bonds with the Si-OH in the hydrolyzed additives, thereby greatly reducing the surface energy of the modified magnetic material, significantly improving the interface compatibility between the modified magnetic material and raw materials such as matrix polyamide, and further improving the dispersion of the modified magnetic material and the compatibility between the modified magnetic material and other raw materials due to the effects of lipophilic long carbon chains, ester groups, and benzene rings. Therefore, the magnetic nylon material of the present invention has stable mechanical properties and stable magnetic properties.
[0028] In addition, due to the combined effect of the highly dispersed modified magnetic material and the modified filler, the amount of water molecule penetration is greatly reduced, so the hydrolysis resistance of the magnetic nylon material of the present invention is enhanced.
[0029] The magnetic nylon material also contains a benzophenone structure and a hindered phenol structure. The benzophenone structure has strong absorption of 320-400nm ultraviolet rays, and because the molecular structure of the benzophenone has good resonance and hydrogen ion transfer effects, the molecular structure will not be destroyed during the absorbent absorbing ultraviolet rays, so it has excellent light stability and can play a long-term protective role for the magnetic nylon material of the present invention. The hindered phenol structure is characterized by two tert-butyl groups distributed on both sides of the phenolic hydroxyl group. This structure with a large steric hindrance effect makes it easy for the hydrogen atoms on the phenolic hydroxyl group to be captured by peroxy free radicals, thereby terminating the chain reaction, or directly combining with active free radicals to generate new relatively stable inert free radicals, thereby protecting the magnetic nylon material of the present invention from oxidation and aging.
[0030] Therefore, the modified magnetic material treated with phosphoric acid and an additive surface enables the magnetic nylon material of the present invention to have excellent and stable hydrolysis resistance, mechanical properties, magnetic properties, and resistance to ultraviolet aging and thermal oxidation aging.
[0031] Furthermore, the lubricant is one or more of polyethylene wax, polypropylene wax, oleamide, erucamide, stearic acid, zinc stearate, silicone, montan wax, and stearamide.
[0032] Furthermore, the modified filler is prepared by the following steps:
[0033] Add inorganic filler and deionized water to a three-necked flask and stir evenly, slowly add concentrated hydrochloric acid to adjust the pH value to 5, stir and heat to 65°C, then slowly add a mixed solution of anhydrous ethanol and coupling agent, keep warm at 65°C for 10 hours after the addition is complete, cool to room temperature after the reaction is completed, filter, wash with anhydrous ethanol 5 times, and finally dry at 80°C for 12 hours to obtain a modified filler; the mass ratio of inorganic filler to coupling agent is 20:1.
[0034] Furthermore, the inorganic filler is one or more of clay, calcium carbonate, talc, mica, wollastonite, barium sulfate, silicon dioxide, aluminum oxide, and calcium oxide.
[0035] Furthermore, the coupling agent is one or more of a silane coupling agent and a titanate coupling agent.
[0036] A method for preparing a high remanence bonded hydrolysis-resistant magnetic nylon material comprises the following steps:
[0037] The raw materials are weighed by weight and added into a high-speed mixer, mixed until there are no obvious lumps or agglomerations, and then put into a twin-screw extruder for melting, blending, extrusion and granulation to obtain a high remanence bonding hydrolysis-resistant magnetic nylon material.
[0038] The beneficial effects of the present invention are as follows: the surface of the modified magnetic material contains hindered phenol structure and benzophenone structure, and the modified magnetic material treated with phosphoric acid and additives has good compatibility with raw materials such as matrix polyamide, and the modified magnetic material can be highly dispersed in the magnetic nylon material to give full play to its own role, and combined with the synergistic effect of other raw materials, the magnetic nylon material of the present invention has excellent and stable hydrolysis resistance, mechanical properties, magnetic properties, resistance to ultraviolet aging and thermal oxidation aging. DETAILED DESCRIPTION
[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] The specific steps for preparing the modified magnetic material are as follows:
[0042] S1. Add 17.1 g of 2,4-dihydroxybenzophenone, 7.2 mL of 3-chloro-1,2-propylene glycol, 11.1 g of potassium carbonate and 180 mL of acetone to a 500 mL dry four-necked flask, stir to dissolve, then heat to 110°C, keep warm for 4 hours, cool to room temperature after the reaction, concentrate, wash three times with deionized water, then wash three times with anhydrous ethanol, concentrate, cool, recrystallize the obtained crude product with ethanol, and finally filter and dry to obtain intermediate 1;
[0043] S2, 22.9g of intermediate 1, 20.9g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 200mL of DMSO were added to a 500mL dry four-necked flask, stirred until completely dissolved, then 2mL of concentrated sulfuric acid was slowly added, the temperature was raised to 100°C with stirring, and the reaction was kept warm for 3h. After the reaction was completed, it was cooled to room temperature, sodium bicarbonate solution was added for neutralization, and the mixture was allowed to stand for stratification after shaking. The organic phase was dried over anhydrous sodium sulfate, filtered, and the filtrate was distilled under reduced pressure, purified by column chromatography (a mixed solvent of cyclohexane and ethyl acetate was selected as the eluent, and the volume ratio of cyclohexane and ethyl acetate was 1:1), and distilled under reduced pressure to obtain intermediate 2;
[0044] S3, nitrogen was blown into a 500 mL dry three-necked flask for 30 min to expel air and moisture in the flask, followed by the addition of 35 mL of bis[3-(triethoxysilyl)propyl]amine, 23.2 mL of tetradecane chloride and 200 mL of DMSO, and then 13.3 mL of triethylamine was slowly added after stirring to dissolve. After the addition was completed, the temperature was raised to 80 ° C and stirred for reaction for 3 h. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure. Purification was performed by column chromatography (a mixed solvent of benzene and ethyl acetate was selected as the eluent, and the volume ratio of benzene and ethyl acetate was 8:2), and distilled under reduced pressure to obtain intermediate 3;
[0045] S4. A 500 mL dry three-necked flask was purged with nitrogen for 30 min to exclude air and moisture, and then 35.2 g of intermediate 2, 37.3 g of intermediate 3, 240 mL of DMF and 0.051 g of tetraisopropyl titanate were added in sequence, the mixture was heated to 90° C. with stirring, and the mixture was kept warm for 24 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, washed with anhydrous ethanol for 3 times, and dried at 80° C. for 12 h to obtain an auxiliary agent.
[0046] S5. Add 20g of NdFeB, 20g of strontium ferrite, 0.04g of phosphoric acid and 200mL of acetone into a dry beaker, heat to 40°C, stir and react for 3h, filter, wash until the filtrate is neutral, and then dry at 80°C for 6h to obtain pretreated magnetic powder; add 0.5g of additive, 10mL of deionized water and 100mL of DMF into a 250mL dry three-necked flask and stir for 1h, then add 20g of pretreated magnetic powder, stir thoroughly until mixed, heat to 70°C, stir and react for 1h, and after the reaction is completed, dry at 100°C for 12h to obtain a modified magnetic material.
[0047] Example 2
[0048] The specific steps for preparing the modified magnetic material are as follows:
[0049] Steps S1-S4 remain unchanged, the mass of phosphoric acid in step S5 is replaced by 0.06 g, and the mass of the auxiliary agent is replaced by 0.75 g, to prepare a modified magnetic material.
[0050] Example 3
[0051] The specific steps for preparing the modified magnetic material are as follows:
[0052] Steps S1-S4 remain unchanged, the mass of phosphoric acid in step S5 is replaced by 0.08 g, and the mass of the auxiliary agent is replaced by 1 g, to prepare a modified magnetic material.
[0053] Example 4
[0054] The specific steps for preparing the modified filler are as follows:
[0055] Add 20g of silicon dioxide and 200mL of deionized water into a 500mL three-necked flask and stir evenly. Slowly add concentrated hydrochloric acid to adjust the pH value to 5, stir and heat to 65°C, then slowly add a mixed solution of 10mL of anhydrous ethanol and 1g of 3-aminopropyltrimethoxysilane. After the addition is completed, keep the temperature at 65°C for 10h. After the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol 5 times, and finally dry at 80°C for 12h to obtain a modified filler.
[0056] Example 5
[0057] The specific steps for preparing the modified filler are as follows:
[0058] Add 10g of calcium carbonate, 10g of talc and 200mL of deionized water into a 500mL three-necked flask and stir evenly. Slowly add concentrated hydrochloric acid to adjust the pH value to 5, stir and heat to 65°C, then slowly add a mixed solution of 10mL of anhydrous ethanol and 1g of isopropyl triisostearate titanate. After the addition is complete, keep the temperature at 65°C for 10h. After the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol 5 times, and finally dry at 80°C for 12h to obtain a modified filler.
[0059] Example 6
[0060] The specific steps for preparing high remanence bonded hydrolysis-resistant magnetic nylon material are as follows:
[0061] 12 parts of nylon 12, 75 parts of the modified magnetic material obtained in Example 1, 0.2 parts of polyethylene wax, 0.3 parts of montan wax, and 2 parts of the modified filler obtained in Example 4 were added to a high-speed mixer and mixed until there were no obvious lumps or agglomerations. The mixture was then put into a twin-screw extruder for melting, blending, extrusion, and granulation to obtain a high remanence, adhesive, hydrolysis-resistant magnetic nylon material.
[0062] Example 7
[0063] The specific steps for preparing high remanence bonded hydrolysis-resistant magnetic nylon material are as follows:
[0064] 20 parts of nylon 1010, 80 parts of the modified magnetic material prepared in Example 2, 0.4 parts of oleic acid amide, 0.4 parts of erucic acid amide, and 2.5 parts of the modified filler prepared in Example 5 were added to a high-speed mixer and mixed until there were no obvious lumps or agglomerations. Then, the mixture was put into a twin-screw extruder for melting, blending, extrusion, and granulation to obtain a high remanence bonding and hydrolysis-resistant magnetic nylon material.
[0065] Example 8
[0066] The specific steps for preparing high remanence bonded hydrolysis-resistant magnetic nylon material are as follows:
[0067] 12 parts of nylon 12, 10 parts of nylon 612, 85 parts of the modified magnetic material obtained in Example 3, 0.3 parts of polyethylene wax, 0.3 parts of zinc stearate, 0.4 parts of stearamide, and 3 parts of the modified filler obtained in Example 5 were added to a high-speed mixer and mixed until there were no obvious lumps or agglomerations. The mixture was then put into a twin-screw extruder for melting, blending, extrusion, and granulation to obtain a high remanence bonding and hydrolysis-resistant magnetic nylon material.
[0068] Comparative Example 1
[0069] Preparation of magnetic nylon material, the specific steps are as follows:
[0070] The remaining steps remain unchanged, only the modified magnetic material of Example 8 is replaced by 42.5 parts of untreated neodymium iron boron and 42.5 parts of untreated strontium ferrite to prepare a magnetic nylon material.
[0071] Comparative Example 2
[0072] The specific steps for preparing magnetic nylon material are as follows:
[0073] The remaining steps remained unchanged, except that the modified filler in Example 8 was replaced by 1.5 parts of untreated calcium carbonate and 1.5 parts of untreated talc to prepare a magnetic nylon material.
[0074] Comparative Example 3
[0075] The specific steps for preparing magnetic nylon material are as follows:
[0076] The remaining steps remain unchanged, and the modified magnetic material of Example 8 is replaced by 42.5 parts of untreated neodymium iron boron and 42.5 parts of untreated strontium ferrite, and the modified filler of Example 8 is replaced by 1.5 parts of untreated calcium carbonate and 1.5 parts of untreated talc to prepare a magnetic nylon material.
[0077] Performance Testing
[0078] The magnetic nylon materials prepared in Examples 6-8 and Comparative Examples 1-3 were subjected to the following performance tests: tensile performance test according to ISO 527, tensile speed of 50 mm / min; bending performance test according to ISO 178, bending speed of 2 mm / min, span of 64 mm; simply supported beam impact strength according to ISO 179 / 1eU; MFR (thermoplastic melt mass flow rate) according to ISO 1133, test temperature of 275°C, load of 2.16 kg; the test results are shown in Table 1:
[0079] Table 1
[0080]
[0081] The magnetic nylon materials obtained in Examples 6-8 and Comparative Examples 1-3 were subjected to dry heat aging at 105°C for 120 hours; UV aging was performed for 120 hours under a 30W UV lamp at room temperature and a vertical irradiation distance of 20 cm; and the tensile stress was tested again. The test results are shown in Table 2 below:
[0082] Table 2
[0083]
[0084] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0085] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high remanence bonded hydrolysis-resistant magnetic nylon material, characterized in that: The method comprises the following raw materials in parts by weight: 12-22 parts of base polyamide, 75-85 parts of modified magnetic material, 0.5-1 parts of lubricant, and 2-3 parts of modified filler; Wherein, the modified magnetic material is prepared by the following steps: S1. Add 2,4-dihydroxybenzophenone, 3-chloro-1,2-propylene glycol, potassium carbonate and acetone to a flask, react at 110°C for 4 hours, cool, concentrate, wash, concentrate again, cool, recrystallize, and finally filter and dry to obtain intermediate 1; S2, add intermediate 1, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and DMSO into a flask, add concentrated sulfuric acid after stirring, react at 100°C for 3h, cool, neutralize, separate, take the organic phase, dry, filter, distill the filtrate under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 2; S3, after nitrogen blowing into the flask, add bis[3-(triethoxysilyl)propyl]amine, tetradecane chloride and DMSO, stir and add triethylamine, react at 80°C for 3h, cool, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 3; S4, after nitrogen blowing into the flask, add intermediate 2, intermediate 3, DMF and tetraisopropyl titanate, react at 90° C. for 24 h, cool, distill under reduced pressure, wash, and dry to obtain an auxiliary agent; S5. Add composite magnetic powder, phosphoric acid and acetone into a beaker, react at 40°C for 3 hours, filter, wash and dry to obtain pretreated magnetic powder; add additives, deionized water and DMF into a flask, stir and add pretreated magnetic powder, react at 70°C for 1 hour, dry to obtain modified magnetic material.
2. The high remanence bonding hydrolysis-resistant magnetic nylon material according to claim 1, characterized in that: The amount ratio of 2,4-dihydroxybenzophenone, 3-chloro-1,2-propylene glycol, potassium carbonate and acetone in step S1 is 17.1 g:7.2 mL:11.1 g:180 mL; the amount ratio of intermediate 1, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, concentrated sulfuric acid and DMSO in step S2 is 22.9 g:20.9 g:2 mL:200 mL; the amount ratio of bis[3-(triethoxysilyl)propyl]amine, tetradecane chloride, triethylamine and DMSO in step S3 is 35 mL:23.2 mL:13.3 mL:200 mL; the amount ratio of intermediate 2, intermediate 3, tetraisopropyl titanate and DMF in step S4 is 35.2 g:37.3 g:0.051 g:240 mL.
3. The high remanence bonding hydrolysis-resistant magnetic nylon material according to claim 1, characterized in that: The mass ratio of the composite magnetic powder to phosphoric acid in step S5 is 20:0.02-0.04; the composite magnetic powder in step S5 is a mixture of neodymium iron boron and strontium ferrite in a mass ratio of 1:
1.
4. The high remanence bonding hydrolysis-resistant magnetic nylon material according to claim 1, characterized in that: The mass ratio of the pretreated magnetic powder to the auxiliary agent in step S5 is 20:0.5-1.
5. The high remanence bonding hydrolysis-resistant magnetic nylon material according to claim 1, characterized in that: The matrix polyamide is one or more of nylon 1010, nylon 12, nylon 11, nylon 612, and nylon 1012.
6. The high remanence bonded hydrolysis-resistant magnetic nylon material according to claim 1, characterized in that: The lubricant is one or more of polyethylene wax, polypropylene wax, oleic acid amide, erucic acid amide, stearic acid, zinc stearate, silicone, montan wax and stearamide.
7. The high remanence bonded hydrolysis-resistant magnetic nylon material according to claim 1, characterized in that: The modified filler is prepared by the following steps: Add inorganic filler and deionized water to a flask and stir, adjust the pH value to 5, then heat to 65°C, add anhydrous ethanol and a coupling agent, react at 65°C for 10 hours, cool, filter, wash, and dry to obtain a modified filler; the mass ratio of the inorganic filler to the coupling agent is 20:
1.
8. The high remanence bonded hydrolysis-resistant magnetic nylon material according to claim 7, characterized in that: The inorganic filler is one or more of clay, calcium carbonate, talc, mica, wollastonite, barium sulfate, silicon dioxide, aluminum oxide, and calcium oxide.
9. The high remanence bonded hydrolysis-resistant magnetic nylon material according to claim 7, characterized in that: The coupling agent is one or more of a silane coupling agent and a titanate coupling agent.
10. The method for preparing a high remanence bonded hydrolysis-resistant magnetic nylon material according to claim 1, characterized in that: The steps include: The raw materials are weighed by weight and added into a high-speed mixer, mixed until there are no obvious lumps or agglomerations, and then put into a twin-screw extruder for melting, blending, extrusion and granulation to obtain a high remanence bonding hydrolysis-resistant magnetic nylon material.
